Climate Change Impact in Charlands in Central Area of Bangladesh: Assessing Vulnerability and Adaptation by the Farming Communities (Journal of Environmental Science and Natural Resources, 2015)
Bangladesh, with an area of 147 thousand km2 and population of 149.78 million, is prone to natural hazards (PHC, 2011). The objectives of the study were to determine the climatic parameter specially temperature and rainfall pattern, assess hazard, vulnerability and adaptation to climate change. Assessment was made during April to June 2013 in char areas of Kazipur upazila under Sirajgonj district. Primary data were collected through Focus Group Discussions and direct observation of the researcher. Secondary data were collected from various publications of government and non-government agencies. Workshops were also conducted at union and upazila level to justify, validate and improve the findings from village levels discussion. Major vulnerabilities faced by the char (island) people were drown of children and old people, lack of safe drinking water, close institutions, crackdown of embankments and roads, river erosion, stagnant water, infertility of cultivable lands, deposits and on crop field, submerse of crops, float away of fishes from ponds, PPR disease of goats, sell cattle at lower price, migration, increase abduction and robbery, increase lightning and cold wave. The major adaptation practiced by the char people was raise homesteads, articulate extra pipes with the tube wells, repair embankments and roads, plant tree seedlings, cultivate advanced crops, vegetables in floating beds, drought tolerant crops, cold wave tolerant and early maturity crop, vaccinate the cattle, drill deep tube wells and reserve fodder (CVCA, 2012).DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22205 J. Environ. Sci. & Natural Resources, 7(2): 59-63 2014